A paisagem cultural do Sítio Arqueológico Piracanjuba, Piraju, SP - Daves, Larissa Figueiredo [UNESP] (2016)
This study aims to present the studies of painted ceramics in the area of three black stains Piracanjuba Archaeological Site, located in the city of Piraju, SP, on the Paranapanema River Valley region, São Paulo side. It is a litho-ceramic site associated with Tradition Tupiguarani . procedures for the production of painted ceramics were investigated in order to understand the possible operational chains of ceramic production, focusing on the answers that geography can give accordingly. The results were published in academic events and the community, in order to improve the analysis of archaeological material on display